2020
DOI: 10.1108/ijhg-07-2020-0085
|View full text |Cite
|
Sign up to set email alerts
|

Quality improvement at East London NHS Foundation Trust: the pathway to embedding lasting change

Abstract: PurposeEast London NHS Foundation Trust (ELFT) is a major provider of mental healthcare and community health services. Quality improvement (QI) has become central to its organisational policy and goals for which it has received national and international attention.Design/methodology/approachThis piece reflects on the Trust's transformation and its approach. It provides many examples and discusses several of the associated challenges in building and sustaining QI momentum. It is the result of a range of perspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 9 publications
2
14
0
Order By: Relevance
“…Sustainability of outcomes was therefore also seen as an important achievement by most authors. This was supported by some of the literature which also indicated that successful QI built legacies mainly through spreading, embedding, and sustaining improvements [78,93,[101][102][103][104][105][106]. This finding was confirmed by impact studies, extensive QI programme evaluations and discussions of overall QI impacts [69, 85, 87, 93, 103-106, 108, 115, 116, 119, 121, 124-126].…”
Section: Stage 8 Resultssupporting
confidence: 53%
See 3 more Smart Citations
“…Sustainability of outcomes was therefore also seen as an important achievement by most authors. This was supported by some of the literature which also indicated that successful QI built legacies mainly through spreading, embedding, and sustaining improvements [78,93,[101][102][103][104][105][106]. This finding was confirmed by impact studies, extensive QI programme evaluations and discussions of overall QI impacts [69, 85, 87, 93, 103-106, 108, 115, 116, 119, 121, 124-126].…”
Section: Stage 8 Resultssupporting
confidence: 53%
“…There was a shared view that quality and patient safety should be more central to QI and investment goals than financial outcomes [72,88,[90][91][92][93][94][95]. This view had not changed over time.…”
Section: Stage 8 Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ELFT provides care to socially diverse and socio-economically deprived catchment area, and achieving sustainable change has proved challenging. The Trust has invested in new training and resources to foster staff motivation, to establish clear and realistic project goals and to promote inclusivity (O'Sullivan et al, 2021).…”
Section: Quality Improvements At East London Nhs Foundation Trustmentioning
confidence: 99%